Analysis of expression characteristics of oil palm EgPRP1 promoter as potential tools for root-trait modification - Masura, Subhi Siti; Shaharuddin, Noor Azmi; Abdul Masani, Mat Yunus; Chan, Kuang Lim; Low, Eng Ti Leslie; Chan, Pek Lan; Rahmah, Abdul Rahman Siti; Abdullah, Mohd Puad; Mohamad Azzeme, Azzreena; Ahmad Parveez, Ghulam Kadir; Abd Rasid, Omar (Springer Science and Business Media, 2026)
Key message: Oil palm EgPRP1 promoter drives targeted gene expression in roots, providing a tool for root-trait modification and improving stress resilience. Abstract: Root-trait modification for crop improvement through genetic engineering requires the availability of strong promoters capable of directing target gene expression in root. In this study, we have characterised the promoter of an oil palm proline-rich protein gene (EgPRP1) and conducted a 5′ serial deletion analysis to delineate the cis-regulatory regions essential for transgene expression in root. The EgPRP1 promoter was shown to be functional in oil palm root tissue through transient expression analysis. Stable transformation in T1 generation tobacco lines further demonstrated that the EgPRP1 construct, the RSP-3A (2000 bp), exhibited strong root-preferential promoter activity across all developmental stages of root growth. Notably, RSP-3A activity was also inducible by wounding, as indicated by localised GUS staining at incision sites on both flowers and leaves of mature transgenic plants. Through fine-scale promoter deletion, RSP-3D, the shortest construct (665 bp), was found to drive root-specific expression in mature root tissues. The results indicated that the promoter contains cis-acting elements functioning as negative regulators, potentially contributing to root specificity. In addition, the 5′ UTR and ATATT motifs that were identified as ROOTMOTIFTAPOX1 elements were essential for strong promoter activity. The findings highlight the potential of the oil palm EgPRP1 promoter as a valuable molecular tool for root-targeted trait modification to improve crop yield, quality, and sustainability.